2004
DOI: 10.1002/pbc.20276
|View full text |Cite
|
Sign up to set email alerts
|

Acremonium pyomyositis in a pediatric patient with acute leukemia

Abstract: Invasive Acremonium infection in humans is rare. We report a patient with leukemia who developed pyomyositis due to Acremonium species. Painful cutaneous nodules and severe myalgia were the first clinical manifestations during the neutropenic stage after chemotherapy. Magnetic resonance image (MRI) revealed multiple nodular lesions scattered along the intramuscular regions of the lower legs. Culture of an aspiration grew Acremonium species. Surgical drainage was performed. Although all antifungal agents tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…In children, disseminated Fusarium infections are still very rare 8–10. Another fungal pathogen, Acremonium (formerly Cephalosporium ), has been reported in a total of 44 cases, with a mortality rate of 30% 11–15. The optimal treatment strategy of these fungal pathogens has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…In children, disseminated Fusarium infections are still very rare 8–10. Another fungal pathogen, Acremonium (formerly Cephalosporium ), has been reported in a total of 44 cases, with a mortality rate of 30% 11–15. The optimal treatment strategy of these fungal pathogens has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…32 Penetrating trauma remains the major cause of primary cutaneous zygomycosis (Table 2). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Other causes reported include elasticized bandages and wound dressings, 55 burns, 56 motor vehicle collision, 57 intravenous access, 58 and dog bite. 59 Our case report of primary cutaneous mucormycosis after a cat bite is a rare finding.…”
Section: Discussionmentioning
confidence: 99%
“…66 The higher overall mortality rate of 29.4% seen in the review of the literature was observed more frequently in patients with neutropenia (60.0%) and without surgical intervention (73.3%), and the survival rate was higher (35.3%) for cases utilizing both antifungal and surgical interventions. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The antifungal agent with the highest survival rate was amphotericin B and its formulations (58.8%). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized infections, such as mycetoma, keratitis, or onychomycosis, are acquired mainly by immunocompetent patients through trauma (5)(6)(7)(8)(9)(10)(11). Invasive infections generally affect immunosuppressed hosts such as those undergoing transplantation or those with AIDS, resulting in a high degree of fatality (12)(13)(14)(15)(16). More rarely, though, invasive infections have also been reported in immunocompetent individuals (17,18).…”
mentioning
confidence: 99%